(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study presents a comprehensive analysis of Scopoletin (Molecule A) and its potential as an inhibitor against HIV-1 reverse transcriptase (HIV-1 RT). Scopoletin, a natural coumarin derivative, was subjected to a detailed investigation of its molecular and pharmacokinetic properties, including composition, structure, molecular flexibility, hydrogen bonding, and various descriptors influencing drug-likeness.The molecular weight of Scopoletin was determined to be within the range of the studied molecules, and it exhibited a moderate proportion of sp3 hybridized carbon atoms (Csp3), indicating a balanced structural composition. Molecular flexibility analysis revealed Scopoletin’s ability to form hydrogen bonds and van der Waals interactions, showcasing its potential to engage in molecular recognition processes.In terms of pharmacokinetic characteristics, Scopoletin displayed a significant affinity for HIV-1 RT in molecular docking studies, particularly in run 20, where it exhibited the highest affinity (-6.853). The analysis of the docking results emphasized the consistent high affinity of Scopoletin, suggesting robust interactions with the target protein.Furthermore, Scopoletin adhered to drug-likeness criteria without breaching core guidelines, exhibiting promising bioavailability values. The molecule also demonstrated inhibitory effects on various enzymes (CYP1A2, CYP2C19, CYP2D6, and CYP3A4) associated with drug metabolism, indicating its potential role in altering pharmacokinetic profiles.However, caution is warranted, as Brenk warnings were triggered by Scopoletin, suggesting potential challenges in synthetic substance acquisition. Despite these warnings, the molecule’s overall drug-likeness and interaction profiles position it as a promising candidate for further development.This study lays the groundwork for future research on Scopoletin as a potential inhibitor of HIV-1 RT, urging further experimental validation, toxicity assessments, and clinical trials to substantiate its therapeutic viability. The robust computational analysis presented herein provides valuable insights for the rational design and optimization of Scopoletin-derived compounds as potential anti-HIV agents.